Home Duino: A Smart Homes Concepts - Ismail, Muhammad Faizal; Ahmad, Mohamad Syafiq; Mohd Ridzuan, Hanis Arina; Mohd Rasman, Siti Nurfarhanah (Penerbit UTHM, 2020)
The smart home has been a feature of science fiction writing for many years but has only become practical since the early 20th Century following the widespread introduction of electricity into the home, and the rapid advancement of information technology. Early remote control devices began to emerge in the late 1800s.